Determinação experimental da solubilidade de orgânicos em água - Malagoni, Ricardo Amâncio (2006)
Solubility data of organic compounds in water have extreme importance for the development of the chemical industry. The design of equipments requires the use of reliable experimental data. The objective of this research work was the development of a methodology to obtain solubility experimental data. The experiments used liquid mixtures containing polar and non-polar components, and were performed at isothermal conditions. A system composed by two cells connected in series was used for determination of solubility experimental data of solutes, especially of organics in water. It comprised two glass recipients named cells, which were connected by a heated stainless steel tube. The pure compound cell had an internal camera where the solute was added. An entrance, at the cell bottom, allowed that the carrier gas N2 to flow taking the solute to the second vase, named saturation cell. Part of the solute was dissolved and another part was thrown away the atmosphere. Liquid samples were taken from the liquid phase, through a silicon septum in the basis of the saturation cell, temporarily until the final saturation. The equilibrium temperature was kept by a thermostatic bath. The liquid sample was analyzed by using a gas chromatograph with a flame ionization detector (FID), and so, obtaining the solutions concentrations. The experiment was finished when the sampled concentration did not change. The results obtained showed a good accordance to our liquid-liquid equilibrium data as well with others from the literature. Solubility data in function of temperature were used to fit the parameters of the equations available in literature.